Sistem Kontrol Pneumatik pada Inlet Guide Vane Turbin Air Mikro Hidro - Ainun Nidhar; Sonki Prasetya (Politeknik Negeri Padang, 2024)
Indonesia has 377 MW of micro-hydro potential as an energy source for electric power generation, with the main component being water turbines. Important parameters controlled in electricity generation are generally the rotation and frequency of the turbine-generator which are regulated automatically in this case through a guide vane. This research explores the potential use of pneumatic control with an Arduino microcontroller as an alternative in regulating the Inlet Guide Valve (IGV) opening in a low-power Micro Hydro Power Plant (MHP). Hydraulic systems that are generally used in large power water turbines have constraints on maintenance costs and high processing time. By utilizing pneumatic control, this research uses Arduino to control the guide vane movement through a pneumatic cylinder. Tests were conducted with separate programs to read the turbine rotation, activate the solenoid valve, and adjust the power on the guide vane simulator. The test results show that the system successfully controls the rotation of the water turbine effectively. The conclusion of this research is that there is an inversely proportional relationship between the opening of the guide vane and the rotation of the water turbine, as well as successful control through a pneumatic system with Arduino. This research contributes to the development of low-power MHP technology with more efficient maintenance costs.